High strength alumina tapes prepared by gel-tape casting method. Issue 5 (1st March 2021) - Stastny, Premysl; Chlup, Zdenek; Castkova, Klara; Trunec, Martin
Abstract: In the current work, high strength alumina (Al2 O3 ) thin tapes were prepared by a novel gel-tape casting method. The water-based slurries were gelled by the polymerization of the epoxy monomers. Low viscosity slurries consisting of nanometer-sized alumina particles were prepared with a solid loading reaching 42 vol%. Sodium and ammonium polyacrylate dispersants were used for alumina particle dispersion and stabilization. The individual Al2 O3 tapes reached a relative density of over 99.5% and a grain size between 1.1 and 1.3 μm after pressureless sintering at 1450 °C. The biaxial strength of sintered samples was measured in the ball-on-three-balls setup and the values of characteristic Weibull strength up to 1400 MPa were obtained for as-sintered tapes with a thickness of about 190 μm. The effect of sodium and ammonium-based polyacrylate dispersants on tape processing and properties of the Al2 O3 tapes were investigated and explained.